The Effect of Motivation, Discipline and Organizational Culture on Employee Performance: The Case of Personnel and Human Resource Development Agency of Palembang City - Pratama, RZ. M. Agang; Idris, Muhammad; Moelyati, Trisniarty Adjeng (International Journal of Marketing & Human Resource Research, 2026)
This study aims to determine the effect of motivation, discipline, and organizational culture on employee performance at the Personnel and Human Resource Development Agency in Palembang City. This research uses associative research. The total number of respondents was 133 BKPSDM employees. Data analysis used multiple linear regression. The research results show that: (1) Motivation, discipline, and organizational culture simultaneously influence motivation, discipline, and organizational culture on employee performance at the Palembang City Personnel and Human Resources Development Agency. (2) In particular, motivation, discipline, and organizational culture. The Influence of Motivation, Discipline, and Organizational Culture on Employee Performance at the Personnel and Human Resources Development Agency of Palembang City.